2015
DOI: 10.2147/ndt.s83569
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive family therapy: an effective approach for cognitive rehabilitation in schizophrenia

Abstract: BackgroundAntipsychotic medication has limited abilities to improve the cognitive impairments that accompany schizophrenia. Adding psychosocial treatment may result in marked improvements in cognitive function, as compared to antipsychotic treatment alone. We hypothesized that a combination of individual and family interventions may be a useful cognitive rehabilitation paradigm for schizophrenia.Materials and methodsAn 18-month follow-up clinical trial of 256 stabilized patients with schizophrenia at six commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…Across all included studies there were a total of 1580 participants with a median sample size of 101, ranging from 45 to 326. Five studies, reported in six papers, were conducted in China [ 35 40 ], two studies were conducted in India [ 41 , 42 ] and Iran [ 43 , 44 ], one study, reported in two papers, was conducted in South Africa [ 45 , 46 ], and one study was conducted in Turkey [ 47 ]. All studies were conducted in upper-middle income countries apart from the two studies based in India, which is classified by the World Bank as lower-middle income.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Across all included studies there were a total of 1580 participants with a median sample size of 101, ranging from 45 to 326. Five studies, reported in six papers, were conducted in China [ 35 40 ], two studies were conducted in India [ 41 , 42 ] and Iran [ 43 , 44 ], one study, reported in two papers, was conducted in South Africa [ 45 , 46 ], and one study was conducted in Turkey [ 47 ]. All studies were conducted in upper-middle income countries apart from the two studies based in India, which is classified by the World Bank as lower-middle income.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies took place in urban areas [ 37 , 43 47 ], two were exclusively in rural areas [ 35 , 36 , 38 ] and one was set across urban and rural sites [ 41 ]. The study location was not indicated in three studies [ 39 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients met the diagnoses of schizophrenia according to the Diagnostic and Statistical Manual of Mental Disorders , Fourth Edition ( DSM -IV) and had no other observable physical disease or other psychiatric disorder aside from schizophrenia. Among them, 254 schizophrenic patients were used to test cognitive function, whose inclusion criteria were based on our previous publications:10,11 1) duration of illness <5 years; 2) has a minimum education of primary middle school; 3) receives atypical antipsychotic monotherapy; 4) has maintained a stable condition for >6 months before entry into the study; and 5) has a positive and negative syndrome scale total score <60.…”
Section: Methodsmentioning
confidence: 99%